IMPLEMENTASI SANKSI TERHADAP PELAKU TINDAK PIDANA PENADAHAN KENDARAAN BERMOTOR: Studi Putusan Nomor. 451/Pid.B/2021/PN.Tjk - Ponco Febri Saputra; Baharudin Baharudin; Anggalana Anggalana (Res Justitia : Jurnal Ilmu Hukum, 2022)
Arrest is a crime that does not stand alone, but a crime that begins with a predicate crime. As for the problem in this research, how is the application of the law to the crime of arresting a motorized vehicle? Decision Number 451/Pid.B/2021/PN.Tjk. ? and What are the Factors Causing the Crime of Arresting Motor Vehicles in Decision Number 451/Pid.B/2021/PN.Tjk.?, the research method used is normative and empirical juridical, the results of research on Application of Law Against the Crime of Arresting Motor Vehicles Decision Number 451/Pid .B/2021/PN.Tjk The Public Prosecutor charged the Defendant with a single charge in accordance with Article 480 Paragraph (1) of the Criminal Code and the Panel of Judges sentenced the defendant Asep Junaedi Bin Abdulah (late) to imprisonment for 1 (one) year and 6 ( six months. Factors Causing the Crime of Arresting Motor Vehicles Decision Number 451/Pid.B/2021/PN.Tjk due to several supporting factors among these factors, namely, educational factors, economic factors, price factors, law enforcement factors and environmental factors, besides that Criminal acts of detention often occur due to the lack of socialization carried out to the community by law enforcement officials directly